Composition of Vaginal microbiota and their antibiotic susceptibility in symptomatic women - Gopalan, Ushadevi; Rajendiran, Sathiyakala; Jayakumar, Karthika; Karnaboopathy, Ranganathan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Bacterial vaginosis is the most prevalent lower genital tract infection in women of reproductive age. The aim of this study was to identify the causative organism in patients with vaginal discharge and to study the sensitivity of the organism to antibiotics. Methods: This was a hospital based prospective study in Department of Obstetrics and Gynecology in a tertiary care hospital over a period of two years. 2062 women with complaints of vaginal discharge were subjected to a high vaginal swab and the sample was cultured, the organisms were identified and antibiotic susceptibility was tested. Results: There was no growth found in 40.7% of patients. E. coli was found to be the most common organism isolated followed by Klebsiella pneumonia and Klebsiella oxytoca. Candida species was isolated in 1.4 % of women. An increased frequency of vaginal infection was found in the age group 26-35 years, followed by age group 36-45 years. 73.2% of the organisms were sensitive to Imipenam, 70.4 % to Amikacin and 65.7% to Gentamycin. There were 10 MRSA strains isolated all of which were sensitive to Vancomycin, Amikacin and Gentamycin. Conclusions: Our study provides information about the different microorganisms present in women with vaginal discharge. Since pathogenic bacteria were more common than Candida species it is recommended to offer treatment to patients after taking a high vaginal swab. Appropriate antibiotics based on culture and sensitivity has to be given along with antifungal agents.